Inside Back Cover: Initial Carbon–Carbon Bond Formation during the Early Stages of the Methanol‐to‐Olefin Process Proven by Zeolite‐Trapped Acetate and Methyl Acetate (Angew. Chem. Int. Ed. 51/2016). Issue 51 (1st December 2016) - Chowdhury, Abhishek Dutta; Houben, Klaartje; Whiting, Gareth T.; Mokhtar, Mohamed; Asiri, Abdullah M.; Al‐Thabaiti, Shaeel A.; Basahel, Suliman N.; Baldus, Marc; Weckhuysen, Bert M.
Abstract : The reaction mechanism of the industrially important methanol‐to‐olefin reaction over zeolite catalysts is investigated. In their Communication onpage 15840 ff., M. Baldus, B. M. Weckhuysen et al. show an effective approach, based on solid‐state NMR spectroscopy and operando UV/Vis spectroscopy, to provide evidence for a direct mechanism concerning the formation of the first carbon–carbon bond during the initial stages of the reaction.